Complexos turísticos imobiliários e governos locais: uso corporativo do território e governança no litoral metropolitano do nordeste brasileiro, no início do século XXI - Silva, Nara Gabrielle de Sousa (2023)
The Tourist Real Estate Complexes are sophisticated structures that bring together, correlated or not, a set of equipment for accommodation, leisure, business, among other services, going beyond the simple association between hotel and holiday ventures, following an urban planning. The objective of this research is to understand the management model of coastal-metropolitan spaces in Northeast Brazil with the presence of Tourist Real Estate Complexes, based on the relationship between Local Governments and the private sector, in the 21st century. The cut is the complexes in operation, using a case study of the Aquiraz Riviera Complex, CE, Brazil. The main procedures, in addition to bibliographic research, are: 1. documentary research; 2. semi-structured interviews with key agents. The dataset is treated in descriptions that support the analysis; tabulation by theme and between the studied CTIs; digital archives for the citation of relevant data; frames and infographics. The dissertation is structured textually in three chapters, after the introduction: 1. Reproduction of the metropolitan coastal space in the 21st century from the Tourist Real Estate Complexes; 2. Governance in new urban spaces: urban policies and the emergence of the local scale; 3. The Aquiraz Riviera and urban governance in Aquiraz, CE. The results demonstrate that the way in which states and municipalities intervene in the real estate development and tourism sector, with different planning practices in relation to development projects, are fundamental for the uneven development design of enterprises in the regional space. The states of Bahia, Pernambuco and Ceará had governments with active practices and policies to attract effective foreign investment, but maintenance takes place through an investment by the governments proportional to the amount attracted. There is evidence that the production of self-segregating undertakings, such as CTIs, reinforce existing socio-spatial inequalities and increase pressure on areas of environmental fragility.